Sagot :
x(x+2)-(2x-1)(x+2)
forme développé : x²+2x-(2x²+4x-x-2)
x²+2x-2x²-4x+x+2
-x²-x+2
forme factorisé : (x+2)(x-(2x-1))
(x+2)(x-2x+1)
(x+2)(-x+1)
forme développé : x²+2x-(2x²+4x-x-2)
x²+2x-2x²-4x+x+2
-x²-x+2
forme factorisé : (x+2)(x-(2x-1))
(x+2)(x-2x+1)
(x+2)(-x+1)
x (x+2) - (2x-1)(x+2)
x²+2x-(2x²+4x-x-2)
=x²+2x-2x²-4x+x+2
=-x²-x+2
(x+2)(-x + 1)
=-x²+x-2x+2
=-x²-x+2
donc x (x+2) - (2x-1)(x+2) est la forme factorisée de (x+2)(-x + 1)
x²+2x-(2x²+4x-x-2)
=x²+2x-2x²-4x+x+2
=-x²-x+2
(x+2)(-x + 1)
=-x²+x-2x+2
=-x²-x+2
donc x (x+2) - (2x-1)(x+2) est la forme factorisée de (x+2)(-x + 1)